SODIUM FLUORIDE INDUCED TOXICITY IN THE KIDNEY OF SWISS ALBINO MICE AND ITS AMELIORATION BY ASCORBIC ACID - I. KHAN; A. RANGA (International Journal of Pharma and Bio Sciences, 2014)
The widespread distribution of fluoride in nature is a direct source of adverse health effects in human population. Fluoride in drinking water is easily absorbed by the intestine and is quickly distributed throughout the body. Fluoride easily crosses the membrane and enters tissues, thus affecting every phase of metabolism. The kidney accumulates more fluoride than all other soft tissues (with the exception of Pineal gland) and is a site for potential fluoride toxicity, since it can be exposed to relatively high concentration of fluoride and this fluoride in kidney is associated with structural and physiological changes. The present study has been carried out to investigate the effect of fluoride toxicity and its amelioration by Ascorbic Acid on the kidney of Swiss albino mice. Adult male mice were treated with 5ppm, 10ppm and 40ppm sodium fluoride (NaF) in drinking water for 7th, 14th, 21st and 28th days until autopsy. Kidney revealed hydropic degeneration, vacuolization, cytoplasmic degranulation in renal tubules and pycnosis in cortical and medullary region. The cessation of NaF treatment could not bring about a complete recovery. However, the administration of Ascorbic Acid to NaF treated mice revealed significant recovery from fluoride toxicity. The effects are transient and reversible with the administration of Ascorbic Acid. So Ascorbic Acid is proposed as an antidotal agent for amelioration of fluoride effects on the kidney.